The phycocyanobilin chromophore of streptophyte algal phytochromes is synthesized by HY2 - Rockwell, Nathan C. (New Phytol, 2017)
Land plant phytochromes perceive red and far-red light to control growth and development, using the linear tetrapyrrole (bilin) chromophore phytochromobilin (PΦB). Phytochromes from streptophyte algae, sister species to land plants, instead use phycocyanobilin (PCB). PCB and PΦB are synthesized by different ferredoxin-dependent bilin reductases (FDBRs): PΦB is synthesized by HY2, whereas PCB is synthesized by PcyA. The pathway for PCB biosynthesis in streptophyte algae is unknown. We used phylogenetic analysis and heterologous reconstitution of bilin biosynthesis to investigate bilin biosynthesis in streptophyte algae. Phylogenetic results suggest that PcyA is present in chlorophytes and prasinophytes but absent in streptophytes. A system reconstituting bilin biosynthesis in Escherichia coli was modified to utilize HY2 from the streptophyte alga Klebsormidium flaccidum (KflaHY2). The resulting bilin was incorporated into model cyanobacterial photoreceptors and into phytochrome from the early-diverging streptophyte alga Mesostigma viride (MvirPHY1). All photoreceptors tested incorporate PCB rather than PΦB, indicating that KflaHY2 is sufficient for PCB synthesis without any other algal protein. MvirPHY1 exhibits a red–far-red photocycle similar to those seen in other streptophyte algal phytochromes. These results demonstrate that streptophyte algae use HY2 to synthesize PCB, consistent with the hypothesis that PΦB synthesis arose late in HY2 evolution.